Core plasma design of the compact helical reactor with a consideration of the equipartition effect. (8th May 2018) - Goto, T; Miyazawa, J; Yanagi, N; Tamura, H; Tanaka, T; Sakamoto, R; Suzuki, C; Seki, R; Satake, S; Nunami, M; Yokoyama, M; Sagara, A
Abstract: Integrated physics analysis of plasma operation scenario of the compact helical reactor FFHR-c1 has been conducted. The DPE method, which predicts radial profiles in a reactor by direct extrapolation from the reference experimental data, has been extended to implement the equipartition effect. Close investigation of the plasma operation regime has been conducted and a candidate plasma operation point of FFHR-c1 has been identified within the parameter regime that has already been confirmed in LHD experiment in view of MHD equilibrium, MHD stability and neoclassical transport.